2003
DOI: 10.1111/j.1443-1661.2004.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective endoscopic study of developmental and configurational changes of early colorectal cancer: Eight cases and a review of the literature

Abstract: Background : A retrospective endoscopic follow-up study was conducted to elucidate the development of minute or superficial-type cancers. Methods : The development of eight colorectal cancers that were followed up by endoscopy was evaluated. Results : (i) Cancer with high-grade atypia frequently developed from lesions diagnosed histologically by biopsy as adenoma; (ii) two polypoid adenomas developed into invasive cancers with non-polypoid configuration; (iii) a superficial elevated-type cancer with high-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Observational studies have shown that when left untreated, NP-CRNs with carcinomas can progress to advanced cancer within a similar time frame. 10,26,27 Once the NP-CRNs become advanced cancer, their appearance is indistinguishable from In situ and submucosal invasive carcinoma…”
Section: Commentmentioning
confidence: 99%
“…Observational studies have shown that when left untreated, NP-CRNs with carcinomas can progress to advanced cancer within a similar time frame. 10,26,27 Once the NP-CRNs become advanced cancer, their appearance is indistinguishable from In situ and submucosal invasive carcinoma…”
Section: Commentmentioning
confidence: 99%
“…Thereafter, some analyses, including retrospective endoscopic analyses, were reported. Because endoscopy can give a much more detailed picture of small lesions, it is suitable for understanding cancer development arising from a minute or superficial type of cancer . In a meta‐analysis of five retrospective radiographic studies of 81 lesions with a final diagnosis of advanced cancer in which the initial lesion was presumed to be early cancer, the initial morphology was 0‐Is in 35 lesions (43.2%) and 0‐IIa in 18 lesions (22.2%).…”
Section: Initial Morphology In Advanced Cancermentioning
confidence: 99%
“…In our multicenter retrospective radiographic studies of 110 cancers, the mean DT was 26.5 months for intramucosal cancer, 25.9 months for submucosal cancer, and 12.3 months for advanced cancer. In a meta‐analysis of radiographic studies, the DT ranged from 9.4 to 55.4 months for intramucosal cancer and 4.7 to 12.2 months for advanced cancer. Colorectal cancer grew rather slowly when the cancer was limited to the mucosa.…”
Section: Growth Speed Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The growth rate of colorectal carcinoma is not constant but accelerates during later stages [13]. Matsui et al [14] retrospectively analyzed and concluded that development of superficialtype cancers were diverse, and sessile-type cancers with marked configuration changes and early cancers developed slowly, although the speed of their growth accelerated according to downward invasion of the cancer. Therefore, the short doubling time of this case-2 months-provides evidence that polypoid-type cancers develop with marked configuration changes.…”
Section: Discussionmentioning
confidence: 98%